A MediaEgo in the MediaPolis: Introduction to an essay concerning changes in communication paradigms in the process of image creation of “new” politicians - Walecka-Rynduch, Agnieszka (Political Preferences, 2017)
The study is aimed to analyse an interesting phenomenon that belongs to the intersection of communicology and media studies and (in the Author’s opinion) has brought into existence a politician with a new type of identity - a MediaEgo. Politicians of this type function in an environment having a special nature for the researcher – in the MediaPolis. The Author, while identifying the determinants (indicata) that constitute a MediaEgo in the researched space (the new public sphere), also observed changes in the communication paradigms that defined communication methods used by candidates to public offices. The Author discusses two new paradigms that illustrate those changes: Communication paradigm 1: new rhetoric, new narration; communication paradigm 2: communication of the image, (not)new media, (not)new communication channels. Key words: MediaEgo, MediaPolis, Image of politicans, mediatisation, communication paradigm